How to write a thesis - Murray, Rowena (Maidenhead : Open University Press, 2011)
Providing down-to-earth guidance to help students shape their theses, the author offers valuable advice and practical tips and techniques. Useful summaries and checklists help students to stay on track or regain their way. Moving beyond the basics of thesis writing, the book introduces practical writing techniques such as freewriting, generative writing and binge writing. Issues such as working out the criteria for your thesis, writer's block, writing a literature review and making notes into a draft are also covered. -- Back cover
"This book has become a trusted resource for students from a wide range of disciplinary backgrounds. Not only does it take you through the steps and stages of thesis writing, but more importantly, it offers rich advice and support that helps build confidence, sets up effective writing habits and generates a positive orientation towards the complex task of thesis writing". (Professor Sarah Moore, Associate Vice President Academic, University of Limerick, Ireland). "I've found Rowena's shrewd and insightful suggestions for writing helpful, not only for others but also for me". (Peter Elbow, University of Massachusetts, Amherst, USA). Providing down-to-earth guidance to help students shape their theses, Rowena Murray offers valuable advice and practical tips and techniques. Useful summaries and checklists help students to stay on track or regain their way. Moving beyond the basics of thesis writing, the book introduces practical writing techniques such as freewriting, generative writing and binge writing. Issues such as working out the criteria for your thesis, writer's block, writing a literature review and making notes into a draft are also covered. The following are new to this edition: New introduction by students - 'How I used this book'; Update on doctoral skills set and Training Needs Analysis; Extended treatment of plagiarism - and how to avoid it; Expanded section on students' well-being; and, Learning outcomes for each chapter.
Includes bibliographical references (p. [313]-321) and index.
Keywords: Dissertations, Academic -- Authorship; Report writing; Academic writing